2018
DOI: 10.1080/02770903.2018.1462377
|View full text |Cite
|
Sign up to set email alerts
|

Self-management behaviors in World Trade Center rescue and recovery workers with asthma

Abstract: Improving World Trade Center-related asthma outcomes will require multifactorial approaches such as supporting adherence to controller medications and other self-management behaviors. This study identified several modifiable beliefs that may be the target of future efforts to support self-management in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Our findings demonstrate that half the enrollees who were prescribed a LTCM were incompletely adherent with their asthma regimen, and that a majority of enrollees had poorly or very poorly controlled asthma as measured by the ACT. Poor adherence is well described in the general asthma literature (23,(41)(42)(43), as well as a previous report of WTC RRW (24). Similarly, poor asthma control in the WTC disaster population has been noted previously (11,17).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Our findings demonstrate that half the enrollees who were prescribed a LTCM were incompletely adherent with their asthma regimen, and that a majority of enrollees had poorly or very poorly controlled asthma as measured by the ACT. Poor adherence is well described in the general asthma literature (23,(41)(42)(43), as well as a previous report of WTC RRW (24). Similarly, poor asthma control in the WTC disaster population has been noted previously (11,17).…”
Section: Discussionsupporting
confidence: 65%
“…Adherence to asthma treatments in adults is generally poor (50% for ICS) (23). Similarly, the only study to date of adherence in WTC RRW with asthma reported 44% (95% CI: 38-50%) overall adherence to asthma control medicines (24).…”
Section: Introductionmentioning
confidence: 99%
“…The absence of peripheral blood Type 2 (T2) inflammatory signals in most of our patients is similar to the findings of Malo et al, who reported on long-term findings in a small group of subjects with irritant-induced asthma [69]. Our findings are also consistent with studies of WTC community members in which low FeNO values or IgE were identified, or in which elevated levels were identified in only a subset of patients with persistent respiratory symptoms [14,16,48,54,55]. The findings are also consistent with studies in firefighters, in which only a subset displayed persistently elevated eosinophil levels associated with decline in lung function [49].…”
Section: Discussionsupporting
confidence: 92%
“…Poor asthma control is usually ascribed to poor adherence with prescribed medications [ 14 , 54 , 55 , 56 , 57 ] and we assumed that many of the persistent symptoms in the WTC EHC patients would be due to failure to use appropriate medications. We therefore presumed that LRS would improve with adherence to a treatment of ICS/LABA and designed a run-in period to confirm adherence before defining study status as Uncontrolled or Controlled.…”
Section: Discussionmentioning
confidence: 99%
“…Measures reducing indoor and outdoor air pollution/irritants exposure, such as high-efficiency particulate air filtration system, can improve indoor air quality by reducing levels of PM 2.5 and particle count [26,27]. In addition, educating enrollees about trigger identification and avoidance may prevent exacerbations and help to improve overall asthma management [13,28,29,30]. Other sociodemographic factors, including older age, lower education level, and higher BMI also contributed to poorer asthma control, consistent with existing literature [2,10,30,31,32].…”
Section: Discussionmentioning
confidence: 99%